Street-connected children with communication disabilities and their caregivers in Western Kenya: experiences, beliefs and needs. Issue 16 (31st July 2021) - Taylor, Carol; Sotiropoulou Drosopoulou, Christina; Rochus, David; Marshall, Julie
Abstract: Purpose: Although street-connected children with communication disability have been identified in Western Kenya, little is currently known about the impact of communication disability on this group. In order to inform future service development, this qualitative study sought to understand the experiences, views and needs of street-connected children with communication disability, and of their caregivers at home and at school. Materials and methods: 13 children, 12 caregivers and 12 school-based Learning Support Assistants participated in interactive sessions, semi-structured interviews and focus groups respectively. Interviews were translated, transcribed and analysed thematically, using framework analysis. Results: Six main themes, with sub-themes, were identified: understanding and awareness of communication disability; the role of others; needs of the children and what might help; impact on those supporting the children; caregiver and Learning Support Assistant needs: support to better help the child; thoughts about the future. Participants' responses highlighted the importance of improving others' attitudes, awareness and willingness to adapt their communication, as well as a need for trusted relationships and some specialist help. Conclusion: Organisations working with street-connected children should take communication disability into account in their services and interventions. Input based on a social model of disability is likely to be acceptable. Implications for rehabilitation: The attitudes and behaviour of others affect how communication disability is experienced by street-connected children and their families. Intervention based on a social model of disability and aimed at improving the communication environment around the child is likely to be acceptable to children, caregivers and education support workers. Caregivers and education support workers want more training and support alongside specialist intervention. Communication at the level of the child is central to building trusted relationships, which are important to the success of street-connected children's rehabilitation and re-integration.